(untitled) (Biological Sciences - PJSIR, 2002)
The objective of thi s study was to note th e effects of some commerci al local detergents such as: chloride bleach , pine disinfectant, powdered soap and bar soap on the fish heart biochemical marker s. Firstly, acclimatization fresh fish into seawater, then runni ng different tria l s to estimate the lethal concentration s, (LDSO) and tolerable limi ts of the fish ,was done. This was followed by studyi ng some of the biochemical parameter s of these fish such as: total lipids, tri glycerides, cholesterol and moi sture contents. Then, the same parameter s tested were compared to control ones. Fi sh behaviour were monitored and recorded. The result obtai ned showed remarkable changes in serum total li pid concentration , cholesterol concentration and triglycerides of fish exposed to different detergents.